Utilization of Uses and Gratifications in Media Use Literature During the Covid-19 Pandemic - Liestia, Maria Natasha (International Journal Labs, 2023)
This research delves into the application of Uses and Gratifications (UGT) theory within the literature analyzing media consumption during the Covid-19 pandemic. Its primary objective is to elucidate and evaluate the usage of UGT in this context, supported by empirical findings and relevant theoretical frameworks. Employing a systematic literature review methodology, the study conducted a literature search in December 2021, utilizing the keywords